Tinjauan Kriminologis Terhadap Penimbunan Bahan Bakar Minyak Bersubsidi Jenis Solar Dan Pertalite Di Kabupaten Belu - Ha'e, Dio Rysardo; Leo, Rudepel Petrus; Amalo, Heryanto (Artemis Law Journal, 2024)
llegal fuel misuse (without a license) is the activity of processing, buying, moving and/or storing fuel oil by buying fuel oil when the fuel oil is still in normal condition. The fuel oil is traded back at an increased price from the normal price.The formulation of this research problem is: (1) What are the factors that cause hoarding of subsidized diesel fuel and pertalite in Belu Regency? (2) What is the modus operandi of hoarding subsidized diesel fuel and pertalite that occurs in Belu Regency? (3) What are the efforts to overcome cases of hoarding of subsidized diesel fuel and pertalite that occur in Belu Regency? This research is empirical juridical research, namely research conducted in the field to find data and information related to the problem: (1) To determine and analyze the factors that cause hoarding of subsidized diesel fuel and pertalite in Belu district. (2) To determine and analyze the modus operandi of hoarding subsidized diesel fuel and pertalite that occurs in Belu Regency. (3) To determine and analyze efforts to overcome cases of hoarding of subsidized diesel fuel and pertalite that occurred in Belu Regency. The results of the analysis obtained in this study are: (1) There are two main factors that cause the hoarding of subsidized fuel oil in Belu Regency, namely internal factors and external factors. Internal factors are the intention of the perpetrator, economic factors and moral and educational factors. External factors such as the ease of obtaining subsidized fuel oil and lack of supervision of illegal fuel.